Mitigating micro-nutrient deficiencies in the diets of rural farm households on the south-central coast of Bangladesh: What roles do the markets and homestead play? - Rahman, Mohammad Zillur; Amjath-Babu, T.S.; Robbani, Mahbub; Mamun-Ur-Rashid, M.; Choudhury, Dipok Kumar; Hasan, Md Fakhrul (Elsevier B.V., 2025)
This study explores the roles of market access and on-farm production in ensuring adequate micronutrient consumption among households in coastal Bangladesh. First, the study employed a 7-day weighed food record method, where respondents documented all food items consumed daily at the household level. These food items were then converted into their corresponding nutritional values to estimate the intake of key nutrients, including protein, crude fiber, fat, calcium, potassium, iron, magnesium, phosphorus, zinc, vitamin A, vitamin C, niacin, riboflavin, thiamin, and folate. Household nutritional requirements were calculated based on the Bangladesh Recommended Dietary Allowances (RDAs), accounting for the age and sex of household members. Nutrient adequacy was assessed by comparing actual nutrient intake against these RDA benchmarks. Second, the study analyzed the determinants of nutrient adequacy using truncated regression models, incorporating relevant socioeconomic and demographic variables. The findings reveal a stark contrast: households meeting RDAs predominantly source their nutrients from markets, highlighting the significance of market accessibility and financial capacity. In contrast, households failing to meet RDAs depend heavily on homesteads, which often lacks dietary diversity and nutrient density. Moreover, the food sources vary depending on the micronutrients in question. Additionally, the study identifies key socio-economic vulnerabilities: younger household heads, often prioritizing crop sales, require greater nutritional awareness; female-headed households face unique barriers to adequate nutrient intake; and households burdened by credit constraints experience reduced consumption of critical nutrients like folate and crude fiber. To address these challenges, the study advocates target group differentiated policy approaches, promoting nutrient-dense crop production, subsidized food safety nets, market-based interventions, credit restructuring, and homestead gardening programs that can attain and long-term nutritional resilience in coastal Bangladesh.